1978
DOI: 10.1111/j.1365-2125.1978.tb01666.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of dobutamine in myocardial infarction for reversal of the cardiodepressive effect of metoprolol.

Abstract: 1 Ten patients with acute myocardial infarction were infused dobutamine in increasing doses up to 15 microgram kg‐1 min‐1. 2 Metoprolol (total dose 15 mg) was then given intravenously to nine of these patients and the beta‐adrenoceptor against effects produced by dobutamine were effectively reversed. 3 Nine patients with acute myocardial infarction pretreated with metoprolol (15 mg) were infused dobutamine 15 microgram kg‐1 min‐1 for 10 min. This resulted in effective reversal of the beta‐adrenoceptor antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In a recent study it was found that dobutamine could reverse all the effects of the (-blocking agent metoprolol in patients with acute myocardial infarction (Waagstein et al, 1978). From animal experiments (Robie et al, 1974) it is known that dobutamine, in addition to its (l-stimulating action, also has a-receptor and P2-receptor stimulating effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study it was found that dobutamine could reverse all the effects of the (-blocking agent metoprolol in patients with acute myocardial infarction (Waagstein et al, 1978). From animal experiments (Robie et al, 1974) it is known that dobutamine, in addition to its (l-stimulating action, also has a-receptor and P2-receptor stimulating effects.…”
Section: Discussionmentioning
confidence: 99%
“…An incidence of VEB of 44% is, however, not higher than expected in patients with recent AM1 (6). As pointed out by Waagstein et al (9), the action of dobutamine is probably energy-demanding, as in patients with "moderately severe" AM1 the shortening of PEPI is associated with an increase in heart rate and BP. However, AM1 patients with more severe signs of pump failure in the above study did not respond with pulse pressure or PEPI but did show a significant increase in heart rate.…”
Section: Resultsmentioning
confidence: 79%
“…The present data from patients with mild left heart failure after AM1 d o not suggest that dobutamine in this situation has significant advantages over isoprenaline, dopamine or noradrenaline. Patients in shock accompanying myocardial infarction also fail to improve with dobutamine infusions (9). However, dobutamine may well be of value during a limited period in pdtients with forward failure due to other conditions than ischemia, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, patient safety may be enhanced by increasing the use of beta-blockers in high-risk patients and perioperative treatment with beta-blockers is now widely advocated [ 33 ]. Up to now, the hemodynamic effect of beta-blocking agents on dobutamine infusion has been controversial [ 34 , 35 ]. In addition, the best fluid replacement therapy, either restrictive or liberal in association with an inotrope, must be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%